Internationalization and the Evolution of Corporate Valuation - Gozzi, Juan Carlos; Levine, Ross; Schmukler, Sergio L. (World Bank, Washington, DC, 2012)
By documenting the evolution of Tobin's q before, during, and after firms internationalize, the authors provide evidence on the bonding, segmentation, and market timing theories of internationalization. Using new data on 9,096 firms across 74 countries over the period 1989-2000, they find that Tobin's q does not rise after internationalization, even relative to firms that do not internationalize. Instead, q rises significantly before internationalization and during the internationalization year. But then q falls sharply in the year after internationalization, quickly relinquishing the increases of the previous years. To account for these dynamics, the authors show that market capitalization rises before internationalization and remains high, while corporate assets increase during internationalization. The evidence supports models stressing that financial internationalization facilitates corporate expansion, but challenges models stressing that internationalization produces an enduring effect on q by bonding firms to a better corporate governance system.